2020
DOI: 10.3390/ijms21145072
|View full text |Cite
|
Sign up to set email alerts
|

Cells Derived from Human Long Bone Appear More Differentiated and More Actively Stimulate Osteoclastogenesis Compared to Alveolar Bone-Derived Cells

Abstract: Osteoblasts derived from mouse skulls have increased osteoclastogenic potential compared to long bone osteoblasts when stimulated with 1,25(OH)2 vitamin D3 (vitD3). This indicates that bone cells from specific sites can react differently to biochemical signals, e.g., during inflammation or as emitted by bioactive bone tissue-engineering constructs. Given the high turn-over of alveolar bone, we hypothesized that human alveolar bone-derived osteoblasts have an increased osteogenic and osteoclastogenic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
5
16
0
Order By: Relevance
“…Indeed, it was shown by Nomura et al (2012) and by Sanchez-Duffhues et al (2019) that PDL fibroblasts are an ideal source for making induced pluripotent stem cells. The morphology of alveolar bone derived cells in vitro is also in agreement with the study by Kelder et al (2020) , in which alveolar bone was compared to long bone cells. In that study, long bone cells presented a more cuboidal appearance, similar to the morphology of osteoblasts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Indeed, it was shown by Nomura et al (2012) and by Sanchez-Duffhues et al (2019) that PDL fibroblasts are an ideal source for making induced pluripotent stem cells. The morphology of alveolar bone derived cells in vitro is also in agreement with the study by Kelder et al (2020) , in which alveolar bone was compared to long bone cells. In that study, long bone cells presented a more cuboidal appearance, similar to the morphology of osteoblasts.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, PDL and alveolar bone cells hardly expressed late osteogenic marker DMP1, an important marker for bone mineralization. Low expression levels of DMP1 were also previously found ( Ruppeka-Rupeika et al, 2018 ; Kelder et al, 2020 ). This might indicate that under these circumstances, cells do not differentiate fully until the late osteoblast/osteocyte stage.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…summarised several studies concluding that there is indeed a physiological difference between osteogenic cells from jawbone versus long bones, making them mandatory for generation of a jawbone model 61 . In line with this, several jawbone models have been proposed based on the origin of the isolated osteoblasts 23 , 25 , 27 , 55 , 62 .…”
Section: Discussionmentioning
confidence: 98%
“…Thus, much scientific attention has been paid to the study of osteoblasts and osteoclasts. Kelder et al reported that osteoblastic cells isolated from long bone showed more significant osteogenic activity than those of alveolar bone [ 7 ]. As the novel molecular mechanisms underlying RANKL induction in osteoblasts, the significant role of LAMP-2, which is involved in the fusion of lysosomes with phagosomes, was discovered by Jansen et al [ 8 ].…”
mentioning
confidence: 99%